Sustainable Transformation of Muslimah Fashion Businesses in Indonesia - Kurniawaty; Muh Said; Syahruddin; Sitti Mujahida Baharuddin (Yayasan Ghalih Pelopor Pendidikan, 2026)
This study examines how consumer sustainability expectations influence green marketing practices and how these practicesstimulate sustainable business model innovation in Muslimah fashion businesses in Indonesia. Using data from 212 owners and senior managers, analysed through Partial Least Squares Structural Equation Modeling, the findings show that sustainability-aware consumers strongly motivate firms to adopt credible green marketing strategies. These strategies then serve as a major driver of sustainability-oriented business model innovation. The results also demonstrate that sustainable business model innovationsignificantly enhances environmental performance, operational resilience, and brand credibility. The study contributes to sustainable fashion scholarship by integrating consumer expectations, marketing practices, and organisational transformation in a culturally specific context where ethical and religious values shape business behaviour. Practical implications highlight the importance of aligning sustainability communication with genuine operational changes to achieve strategic and performance benefits.